2010
DOI: 10.1017/s0003055409990384
|View full text |Cite
|
Sign up to set email alerts
|

Building Strategic Capacity: The Political Underpinnings of Coordinated Wage Bargaining

Abstract: The coordination of wage bargaining has been used to explain everything from inequality to unemployment in rich democracies. Yet there has been little theoretical work and almost no quantitative empirical work exploring the determinants of bargaining coordination. Others hypothesize that centralized bargaining depends on the ability of peak associations to control the strike activities of their affiliates. I argue formally that more unequally distributed resources across unions should inhibit the centralizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…In particular, we do not provide a sufficient set of conditions for skilled unions consenting to coordinated and solidaristic bargaining. In accounting for this phenomenon, the existing literature has variously emphasized the role of complementarities between skilled and unskilled workers (Wallerstein 1990), the collective gains from controlling wage inflation (Iversen 1995; Katzenstein 1985), the distribution of strike capacity across unions (Ahlquist 2010), and (most important, in our view) the capacity of employers in the export sector to impose coordination in order to reduce the cost of skilled labor (Swenson 1991; Thelen 2004). These factors (employer preferences, in particular) have probably also played a role in the shift away from highly centralized bargaining in some countries, but our model is designed to explain the consequences of these shifts, not their causes.…”
Section: An Institutional Model Of Real Exchange Rates and Competitivmentioning
confidence: 99%
“…In particular, we do not provide a sufficient set of conditions for skilled unions consenting to coordinated and solidaristic bargaining. In accounting for this phenomenon, the existing literature has variously emphasized the role of complementarities between skilled and unskilled workers (Wallerstein 1990), the collective gains from controlling wage inflation (Iversen 1995; Katzenstein 1985), the distribution of strike capacity across unions (Ahlquist 2010), and (most important, in our view) the capacity of employers in the export sector to impose coordination in order to reduce the cost of skilled labor (Swenson 1991; Thelen 2004). These factors (employer preferences, in particular) have probably also played a role in the shift away from highly centralized bargaining in some countries, but our model is designed to explain the consequences of these shifts, not their causes.…”
Section: An Institutional Model Of Real Exchange Rates and Competitivmentioning
confidence: 99%
“…In line with this new understanding of labor market change, we argue that technological change-induced labor market polarization creates a new economic cleavage between high- and low-skill workers over support for unions that impacts both trade union density and the coverage of collective agreements. Our theory follows recent work in political science on institutional development, which has shown that greater between-group heterogeneity decreases the probability of developing encompassing institutions (Ahlquist, 2010; Lupu and Pontusson, 2011). The polarization of employment into high- and low-wage occupations and “hollowing out” of the middle part of the wage distribution may affect both individual preferences for unionization and the distribution of preferences for unionization across the skill spectrum.…”
Section: Labor Market Polarization and Collective Agreementsmentioning
confidence: 72%
“…Research on the golden age of capitalism in developed democracies, for example, considers the effects of unions and unionemployer relationships on wage levels, wage dispersion, and working conditions. Labor unions also influence electoral outcomes, work closely with left-leaning political parties to influence social policy and the distribution of income, and determine the effectiveness of monetary policy via wage restraint and coordinated wage bargaining (Ahlquist 2010, Hall & Soskice 2001, Iversen 1999. Union members and leaders interact strategically with employers and political officials, deciding when to strike (Franzosi 1995, Golden 1997) and when to take action on issues that fall outside of their direct purview (Ahlquist & Levi 2013).…”
Section: The Effects Of Global Production On Labor: Theory and Evidencementioning
confidence: 99%